Experimental production of an irreversible type of ascites - Fernández Naone, Gonzalo; Girardi, Gino; Blanco, Jorge; Pereira, Mónica; Bracco, Isabel; Bonaba, Roberto (Cirugía del Uruguay, 1984)
By partial constriction of the intrathoracic inferior vena cava a type of ascites was induced in dogs. In a short time, persisten! ascites was produced, accompanied with distal edema, with a low post-operative death rate and without evident impairment of the renal func• tion but seriously affecting nutritional conditions.